2013
DOI: 10.1016/j.ridd.2013.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Gait stability in children with Cerebral Palsy

Abstract: Children with unilateral Cerebral Palsy (CP) have several gait impairments, amongst which impaired gait stability may be one. We tested whether a newly developed stability measure (the foot placement estimator, FPE) which does not require long data series, can be used to asses gait stability in typically developing (TD) children as well as children with CP. In doing so, we tested the FPE’s sensitivity to the assumptions needed to calculate this measure, as well as the ability of the FPE to detect differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 31 publications
(51 reference statements)
0
37
1
Order By: Relevance
“…The locomotor patterns exhibited by children with CP have been widely studied in terms of lower limb kinematics, using a classical gait analysis approach [ 14 ]. The control of upper body movements during gait has also been assessed in children with CP, either using motion analysis [ 15 , 16 ], or by adopting musculoskeletal models such as the foot placement estimator [ 17 ]. Increased ranges of motion in head and trunk movements have been observed in each anatomical plane during gait [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The locomotor patterns exhibited by children with CP have been widely studied in terms of lower limb kinematics, using a classical gait analysis approach [ 14 ]. The control of upper body movements during gait has also been assessed in children with CP, either using motion analysis [ 15 , 16 ], or by adopting musculoskeletal models such as the foot placement estimator [ 17 ]. Increased ranges of motion in head and trunk movements have been observed in each anatomical plane during gait [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, other authors previously suggested a possible influence of walking speed on gait stability. However, the exact relationship remains unclear (Dingwell and Marin, 2006 ; England and Granata, 2007 ; Bruijn et al, 2009 , 2013b ), especially in children with cerebral palsy. Therefore, current study aimed to examine the influence of increasing walking speed on gait stability in typically developing children, children with bilateral cerebral palsy and children with unilateral cerebral palsy.…”
Section: Introductionmentioning
confidence: 99%
“…They were recruited from CP children referring to Neurology centers in Isfahan City, Iran, using convenience sampling method. Inclusion criteria were having spastic diplegic CP, ability to stand and walk independently, no use of walker or other assistive devices, no history of lower limbs and trunk surgery affecting walking, ability to follow the verbal instructions, no history of treatment with botulinum toxin within the last 6 months [3], and being categorized at level II or III based on Gross Motor Function Classification System (GM-FCS). An informed consent form was obtained from the parents of the children before conducting any measurement.…”
Section: Methodsmentioning
confidence: 99%
“…The postural balance in children with CP is weak and puts them at risk of falling [2]. However, few studies have been conducted on the dynamic balance of walking in children with CP [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation